2019
DOI: 10.1002/jcc.26139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Solute Cavity on the Solvation Energy and its Derivatives within the Framework of the Gaussian Charge Scheme

Abstract: The treatment of the solvation charges using Gaussian functions in the polarizable continuum model results in a smooth potential energy surface. These charges are placed on top of the surface of the solute cavity. In this article, we study the effect of the solute cavity (van der Waals‐type or solvent‐excluded surface‐type) using the Gaussian charge scheme within the framework of the conductor‐like polarizable continuum model on (a) the accuracy and computational cost of the self‐consistent field (SCF) energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 53 publications
(108 reference statements)
0
126
0
2
Order By: Relevance
“… a Using a Gaussian charge scheme and a scaled van der Waals surface. 101 b An additional two protons are added to cap residues 423 His and 257 Cys . c The RMSD is defined as the deviation of the [VFe 7 S 8 C(XO 3 )] part with respect to both cofactors in the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“… a Using a Gaussian charge scheme and a scaled van der Waals surface. 101 b An additional two protons are added to cap residues 423 His and 257 Cys . c The RMSD is defined as the deviation of the [VFe 7 S 8 C(XO 3 )] part with respect to both cofactors in the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the calculations used the RIJCOSX [32][33][34] approximation for computational efficiency 35 together with the SARC/J 36,37 auxiliary basis set. Solvent effects (acetonitrile, MeCN) were taken into account in the optimizations using the C-PCM Gaussian charge scheme 38,39 continuum solvation model. Frequency calculations showed that the optimized structures correspond to minima (no imaginary frequency).…”
Section: Methodsmentioning
confidence: 99%
“…The SwiG implementation of PCMs first appeared in the Q‐ Chem program, 241 and was extended recently to discretize not only the vdW and SAS cavities but also the SES 25 . Related discretization schemes have since been adopted in other software 242,243 . While alternative discretization methods have been described subsequently, 244–247 it is unclear whether these have been formulated with gradients in mind.…”
Section: Methodsmentioning
confidence: 99%
“…25 Related discretization schemes have since been adopted in other software. 242,243 While alternative discretization methods have been described subsequently, [244][245][246][247] it is unclear whether these have been formulated with gradients in mind. Given the simplicity and success of the SwiG approach, it is also unclear what is to be gained from these formulations.…”
Section: Discretizationmentioning
confidence: 99%